Development and evaluation of pH sensitive semi-interpenetrating networks: assessing the impact of itaconic acid and aloe vera on network swelling and cetirizine release - Ajaz, Nyla; Bukhsh, Munnaza; Kamal, Yousaf; Rehman, Fauzia; Irfan, Muhammad; Khalid, Syed Haroon; Asghar, Sajid; Rizg, Waleed Y.; Bukhary, Sahar M.; Hosny, Khaled M.; Alissa, Mohammed; Safhi, Awaji Y.; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
Hydrogels are crosslinked three-dimensional networks, and their properties can be easily tuned to target the various segments of the gastrointestinal tract (GIT). Cetirizine HCl (CTZ HCl) is an antihistaminic drug, which when given orally can upset the stomach. Moreover, this molecule has shown maximum absorption in the intestine. To address these issues, we developed a pH-responsive semi-interpenetrating polymer network (semi-IPN) for the delivery of CTZ HCl to the lower part of the GIT. Initially, 10 different formulations of itaconic acid-grafted-poly (acrylamide)/aloe vera [IA-g-poly (AAm)/aloe vera] semi-IPN were developed by varying the concentration of IA and aloe vera using the free radical polymerization technique. Based on swelling and sol-gel analysis, formulation F5 containing 0.3%w/w aloe vera and 6%w/w IA was chosen as the optimum formulation. The solid-state characterization of the optimized formulation (F5) revealed a successful incorporation of CTZ HCl in semi-IPN without any drug-destabilizing interaction. The in vitro drug release from F5 showed limited release in acidic media followed by a controlled release in the intestinal environment for over 72 h. Furthermore, during the in vivo evaluation, formulation F5 did not affect the hematological parameters, kidney, and liver functions. Clinical observations did not reveal any signs of illness in rabbits treated with hydrogels. Histopathological images of vital organs of treated animals showed normal cellular architecture. Thus, the results suggest a non-toxic nature and overall potential of the developed formulation as a targeted drug carrier.